A Narrative Exposition on Public Toilet Usage by Women: A Study from Warangal. (February 2019) - Reddy, Y. Malini; Raghavan, Srividya; Vedala, Srinivas Chary
Despite the heightened emphasis on the sanitation agenda of the country, driven by both international and national development goals, there is little scholarly work to base our understanding of infrastructural needs of users for effective implementation. This research was conceived as a part of an extended study to assess sanitation needs in the city of Warangal, Telangana, India. The aim of this study is, specifically, to understand the needs of women for public toilets (PTs) and sanitation facilities. This article presents the results from the analysis of interviews conducted among a cross section of women from various walks of life, and of different ages and qualifications. The interviews were subjectively parsed and interlinked by two independent women reviewers unacquainted with the project. The raw qualitative data was then text analysed, and networks were created to map the co-occurring concepts. This exercise led to the revelation that there is a need for (a) toilets with basic facilities exclusively for women; (b) caretakers who will collect user charges, keep the toilets clean and provide a semblance of security; (c) well-maintained sanitation facilities in places such as bus stops and railway stations and (d) easy accessibility of PTs on main roads and in busy commercial areas.